How the magnetic field impacts the chiroptical activities of helical copper enantiomers. (15th October 2021) - Wu, Jialu; Li, Bo; Wang, Hong; Lai, Yingzhen; Ye, Yue; Zou, Yongkang; Tian, Jumei; Xu, Yaohua
Abstract : A pair of enantiomers [Cu(l -pro)(l -tyr)]·2H2 O n (L-1 ) and [Cu(d -pro)(d -tyr)]·2H2 O n (D-1 ) based on the chiral ligands l /d -proline and l /d -tyrosine were synthesized and investigated using single-crystal X-ray structure analysis, IR, thermogravimetric analysis, solid-state UV-Vis spectroscopy, circular dichroism, magnetic studies, and DFT calculations. Abstract : A pair of enantiomers [Cu(l -pro)(l -tyr)]·2H2 O n (L-1 ) and [Cu(d -pro)(d -tyr)]·2H2 O n (D-1 ) based on the chiral ligands l /d -proline and l /d -tyrosine were synthesized and investigated using single-crystal X-ray structure analysis, IR spectroscopy, thermogravimetric analysis, solid-state UV-Vis spectroscopy, circular dichroism, magnetic studies, and DFT calculations. The enantiomers L-1 and D-1 showed left and right-handed helicity, respectively. The magnetic studies indicated that they both showed weak ferromagnetic characteristics. In order to examine the chiroptical activities, we measured the solid-state CD and MCD spectra, which were both of opposite sign for the enantiomers. Compared to the CD spectra, the MCD signals for L-1 and D-1 are intensified at ∼500 nm and weakened at ∼700 nm, which is interesting and needs in-depth research. The further DFT calculations revealed that the magnetic field might directly influence the d yz orbital of the copper and π orbitals of the ligands to increase the electron density and intensify the CD absorption at about 500 nm, impact the d z 2 orbital of the copper and π* orbitals of the ligands to decrease the electron density and lower the intensity of CD absorption at around 700 nm, which provides a new threshold for experimentalists and theoreticians to comprehend the magnetism and optics interaction in orbitals. The experimentally and theoretically investigated results are useful for deliberately boosting and weakening the circular dichroism signals in magnetically controlled technologies.